The Statistical Atlases of the Baltic States 1918–1940: The First National Atlases of the Three Newly Independent Countries. (3rd April 2018) - Schulz, Thomas
ABSTRACT: When 'classical' statistical atlases in Western Europe and North America had already seen their heyday by the end of the First World War and were in decline, newly independent nations in Eastern Europe and elsewhere revived the idea of issuing atlases as marketing instruments as their new nations were shaped and the first census results became available. Amongst them were the three Baltic States, Estonia, Latvia and Lithuania. Only a few years after finally gaining independence in 1918, five substantial statistical atlases had been issued in Riga, Tallinn and Kaunas. They offered for the first time a visual portrait of the new countries and their political, social and economic situations in an equally attractive and completely fact-based manner. This paper gives an overview of the structure, content and cartographic design of the atlases. The historical context and rationale for issuing the atlases are examined, as well as their place in the wider history of statistical and national atlases.